O prawie dostępu do informacji publicznej w kontekście przemian cywilizacyjnych ‒ kilka refleksji - Olejniczak-Szałowska, Ewa (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego)
The right to access to public information is a public subjective right established by the Article 61 of the Constitution of the Republic of Poland and specified by further acts of law, in particular by the Act of 6 September, 2001 on access to public information. The paper considers the selected problems regarding the exercise of this right by the citizens in a form of submitting the application for access to public information. In particular, it discusses the issue of admissibility of submitting the applications in electronic form and effectiveness of such applications.
Keywords: provision of information in electronic form; public subjective right; application for access to public information; access to public information